2001
DOI: 10.1007/bf02287772
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of stressors and co-morbid mental health problems that contribute to youths' paths to substance-specific services

Abstract: Substance-specific services are tailored to address the inappropriate use of chemicals such as alcohol and marijuana. Unfortunately, few teens ever access such need-based services. This article explores the paths to substance-specific service use in a sample of urban adolescents who are public service sector users: a direct path from substance misuse and an indirect path from general mental health service use. Results indicate that even though a significant percentage of youths frequently consume substances an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 39 publications
1
17
0
1
Order By: Relevance
“…To date, 3 studies have examined perceived barriers to substance abuse treatment among detained youth. [22][23][24] Kim and Fendrich 22 and Lopez 23 found that seeking services for substance abuse was determined by the perceived need for treatment, regardless of race/ethnicity. Johnson and colleagues 24 found that beliefs that one could handle one's own problems or that problems would simply go away were associated with lower rates of service use among juvenile detainees.…”
Section: Introductionmentioning
confidence: 99%
“…To date, 3 studies have examined perceived barriers to substance abuse treatment among detained youth. [22][23][24] Kim and Fendrich 22 and Lopez 23 found that seeking services for substance abuse was determined by the perceived need for treatment, regardless of race/ethnicity. Johnson and colleagues 24 found that beliefs that one could handle one's own problems or that problems would simply go away were associated with lower rates of service use among juvenile detainees.…”
Section: Introductionmentioning
confidence: 99%
“…31,41 Other studies have pointed to (usually long-term) use of alcohol as a culprit in increases in symptoms of depression over time. 29,42 Still others have emphasized the likelihood that there exist environmental 43,44 and/or genetic factors, 45-48 which tend to significantly increase individuals' vulnerability to both types of disorders.…”
Section: Introductionmentioning
confidence: 99%
“…31,41 Other studies have pointed to (usually long-term) use of alcohol as a culprit in increases in symptoms of depression over time. 29,42 Still others have emphasized the likelihood that there exist environmental 43,44 and/or genetic factors, 45-48 which tend to significantly increase individuals' vulnerability to both types of disorders.Factors that have been found to be related to early alcohol use initiation include male gender, 49-51 low levels of parental monitoring, 52,53 frequent parental alcohol use, 54,55 parental emotional disorders, 56,57 child abuse, 58 and poor parent-child relationships, 50,59 as well as child novelty-seeking tendencies 60 and conduct disorder symptoms. 8,61 Some of these factors have also been found to be associated with depressive symptoms.…”
mentioning
confidence: 99%
“…Economic obstacles can take many forms in their impact on whether or not substance-specific services are utilized by Hispanic youth. Some youth may not have the availability of needed services (Johnson, Stiffman, Hadley-Ives, & Elze, 2001). Even when these services are available, additional economic obstacles can hinder service utilization by Hispanic adolescents (Pumariega et al, 1998).…”
Section: Socio-demographic Variablesmentioning
confidence: 99%